Leveraging ChatGPT to Enhance Article Publication: A Strategic Initiative for Advancing Academic in Higher Education - Daulay, Sholihatul Hamidah; Nabila , Afanin; Dalimunte , Muhammad; Daulay , Ernita (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study examines the potential of ChatGPT, an AI-driven conversational model, to enhance student academic writing in higher education. In response to the increasing demand for advanced writing competencies, the research explores ChatGPT’s role as a support tool for developing students' writing skills. It critically analyzes the benefits, challenges, and ethical implications of AI-assisted writing, offering insights and recommendations for educators, institutions, and students. The study aims to contribute to the discourse on integrating AI in academic development by highlighting ChatGPT’s potential and limitations in improving writing quality within higher education contexts. The strategic utilization of ChatGPT should constitute an indispensable element of a comprehensive academic strategy that amalgamates technological innovation with robust mentorship, the cultivation of a research-oriented culture, and ethical education.